Carrier-free nanodrugs with efficient drug delivery and release for cancer therapy: From intrinsic physicochemical properties to external modification - Heng Mei (KeAi Communications Co., Ltd., 2022)
The considerable development of carrier-free nanodrugs has been achieved due to their high drug-loading capability, simple preparation method, and offering “all-in-one” functional platform features. However, the native defects of carrier-free nanodrugs limit their delivery and release behavior throughout the in vivo journey, which significantly compromise the therapeutic efficacy and hinder their further development in cancer treatment. In this review, we summarized and discussed the recent strategies to enhance drug delivery and release of carrier-free nanodrugs for improved cancer therapy, including optimizing the intrinsic physicochemical properties and external modification. Finally, the corresponding challenges that carrier-free nanodrugs faced are discussed and the future perspectives for its application are presented. We hope this review will provide constructive information for the rational design of more effective carrier-free nanodrugs to advance therapeutic treatment.